Formate hydrogen lyase mediates stationary-phase deacidification and increases survival during sugar fermentation in acetoin-producing enterobacteria - Vivijs, Bram; Haberbeck, Leticia U.; Baiye Mfortaw Mbong, Victor; Bernaerts, Kristel; Geeraerd, Annemie H.; Aertsen, Abram; Michiels, Chris W. (Frontiers in Microbiology, 2015)
Two fermentation types exist in the Enterobacteriaceae family. Mixed-acid fermenters produce substantial amounts of lactate, formate, acetate and succinate, resulting in lethal medium acidification. On the other hand, 2,3-butanediol fermenters switch to the production of the neutral compounds acetoin and 2,3-butanediol and even deacidify the environment after an initial acidification phase, thereby avoiding cell death. We equipped three mixed-acid fermenters (Salmonella Typhimurium, S. Enteritidis and Shigella flexneri) with the acetoin pathway from Serratia plymuthica to investigate the mechanisms of deacidification. Acetoin production caused attenuated acidification during exponential growth in all three bacteria, but stationary-phase deacidification was only observed in Escherichia coli and Salmonella, suggesting that it was not due to the consumption of protons accompanying acetoin production. To identify the mechanism, 34 transposon mutants of acetoin-producing E. coli that no longer deacidified the culture medium were isolated. The mutations mapped to 16 genes, all involved in formate metabolism. Formate is an end product of mixed-acid fermentation that can be converted to H2 and CO2 by the formate hydrogen lyase (FHL) complex, a reaction that consumes protons and thus can explain medium deacidification. When hycE, encoding the large subunit of hydrogenase 3 that is part of the FHL complex, was deleted in acetoin-producing E. coli, deacidification capacity was lost. Metabolite analysis in E. coli showed that introduction of the acetoin pathway reduced lactate and acetate production, but increased glucose consumption and formate and ethanol production. Analysis of a hycE mutant in S. plymuthica confirmed that medium deacidification in this organism is also mediated by FHL. These findings improve our understanding of the physiology and function of fermentation pathways in Enterobacteriaceae.